Application of intelligent technologies in the problems of election of the leader in youth environment - Kondratenko, N. R.; Cherniakhovych, T. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The possibility of application of intelligent technologies for election of youth leader is considered. The technique of knowledge obtaining in the form of fuzzy rules "IF-THEN" with further possibility of their processing by means of fuzzy logic is suggested.